Production of Bio hydrocarbons from Vegetable Oils and Animal Fats Using Magnesium Oxide as Catalyst - Siregar, Yusraini Dian Inayati; Riyadhi, Adi; Damayanti, Widya Anggun; Rizkiansyah, Rizkiansyah; Murditya, Muhammad Bagas (Syarif Hidayatullah State Islamic University, 2023)
Bio hydrocarbons are renewable fuels that can be produced through the catalytic deoxygenation of fatty acids, resulting in compositions like gasoline, kerosene, and diesel fractions derived from petroleum. The objective of this study is to generate gasoline, kerosene, and diesel from vegetable oils and animal fats using an MgO catalyst synthesized through the calcination of Mg-citrate. The characterization of the MgO catalyst, employing Fourier Transform Infrared (FTIR), X-Ray Diffraction (XRD) and Brunauer-Emmett-Teller (BET) surface adsorption method, revealed the presence of crystalline MgO and showed that mesoporous MgO with average pore size of 15.52 nm and exhibiting a surface area of 35.68 m2 g-1. The MgO catalyst was utilized in the deoxygenation reaction of palm oil, palm wax, and chicken fat, leading to the production of bio hydrocarbons with paraffin and olefin compositions like those found in gasoline, kerosene, and diesel derived from petroleum. Gas Chromatography-Mass Spectroscopy (GCMS) analysis of the liquid product demonstrated that the highest quantity of gasoline was derived from palm wax, followed by palm oil and chicken fat. Palm wax exhibits promising potential as a raw material for gasoline production through the deoxygenation reaction, specifically through decarboxylation and decarbonylation processes facilitated by the MgO catalyst.